Linoleic Acid Isolation from Watermelon Seeds Oil (Citrullus lanatus L) with Urea Inclusion Method - Divina Anindya Della; Hartati Soetjipto; November Rianto Aminu (Department of Chemical Education Faculty of Teacher Training and Education Universitas Su, 2022)
Nutritional problems still become a crucial issue in Indonesian public health. Fulfillment of nutritional balance is expected to improve life quality. In humans, one of the nutrients that play a role in the growth of brain and nervous system functions is PUFA, such as omega-6 and omega-3. Besides, fulfillment of nutritional balance can prevent some diseases; especially linoleic acid used to prevent some diseases. Linoleic acid is an omega-6 and essential fatty acid. Linoleic acid is the main essential fatty acid because it is the precursor for GLA, DGLA, and AA. Omega-6 works with omega-3 and some omega-3 benefits are supported or can arise by omega-6 presence. Studies reveal that watermelon contains high linoleic acid. This study aimed to determine the optimum temperature and ratio of fatty acids: urea for the isolation of linoleic acid from watermelon seed oil. The method used was urea inclusion with a variety of temperatures (-6oC, 6oC, 18oC) and the ratio of fatty acid: urea (1:1; 1:3; 1:5). The results showed the optimum watermelon seed oil linoleic acid isolate at 18oC and the ratio of fatty acids: urea 1:5 with linoleic acid purity (%) of 82.53%.